A comparative hydrochemical study of bottled mineral waters - Bonotto, Daniel Marcos [UNESP] (2020)
In the last few decades, the consumption of natural drinking water, either spring or mineral (bottled or not), increased in several countries. Despite drinking water being mostly used as the tap water accessible in every household, many people believe that naturally occurring waters are healthy and/or can be utilized for health remedies, thus, exhibiting better quality than the tap water. Additionally, economic reasons have also favored their use as bottled waters therefore widely increasing the commercialization of mineral waters. Thermal and mineral waters use in Brazil is not recent due to arrival of European immigrants, mainly from Portugal. The construction of thermal and non-thermal spas for therapeutic and leisure purposes reached a maximum number in the 1930s and 1950s, mainly at São Paulo (SP) and Minas Gerais (MG) states. The Brazilian Code of Mineral Waters (BCMW) was established in this time, under French influence, by Register 7841 published on 8 August 1945. The BCMW classifies the mineral and potable waters for uses in spas and bottling purposes. There are several parameters considered by the BCMW, for instance, the radioactivity due to dissolved 222Rn and 220Rn. EuroGeoSurveys (The Geochemistry Group of the European Geological Surveys) managed a common European sampling campaign of bottled mineral and spring waters (analysis of 884 samples for more than 70 chemical parameters in one laboratory) whose results were published in 2010. The hydrogeochemical study held within the framework of the project involved different approaches like analytical techniques, major constituents, trace elements, radionuclides, stable isotopes, mapping, waters classification, statistical treatment of hydrochemical data, human health, etc. This chapter reports a comparative hydrochemical study of mineral waters bottled in different countries based on Brazilian and international guidelines with the aim of increasing the information generated by EuroGeoSurveys.